Do adolescents eat healthy: Diet quality dimensions and fish consumption in low-income urban Bangladesh - Akter, Mahsina Syeda (Wageningen University & Research, 2024)
This doctoral dissertation from WUR was partially funded by the CGIAR Trust Fund (via A4NH, now SHiFT). It is under embargo.